Massive Open Online Course (MOOC) Among the Science of Thinking and Ethics Students - Ku Zolidia Ku Mahamad, Mardzelah Makhsin and Mohd Kasri Saidon (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to identify the level of Massive Open Online Courses (MOOC) skill among the Science of Thinking and Ethics students. This matter is appropriate with Pelan Pembangunan Pendidikan Malaysia (PPPM) 2013-2025 which has outlined the eleven shifts and one of those is to benefit the usage of ICT in improving the learning quality in Malaysia. This study adopts survey research method to study Science of Thinking and Ethics students’ perception towards the use of MOOC. This study is a systematic study in terms of design, development and evaluation process from the aspects of readiness, performance, initiative, influence, facilities and barriers in the MOOC development for the Science of Thinking and Ethics course. 77 students were involved in the study representing students from College of Arts and Sciences (CAS), College of Business (COB), and College of Law, Government and International (COLGIS). The findings showed that the level of facility in UUM supported the MOOCs learning in the Science of Thinking and Ethics course. The findings also showed that the barrier in using MOOC was very low. This indicates that UUM students were ready and supported MOOC learning in the Science of Thinking and Ethics course. Furthermore, as far as the students’ performance is concerned, the students agreed that MOOCs learning was effective for teaching and learning. MOOC also helped in increasing the achievement in the course and the usage of MOOC enabled new opportunities for students to follow long distance learning through the use of technology and helped in providing experience to the students to learn online the Science of Thinking and Ethics course.